2014
DOI: 10.1021/ja503301m
|View full text |Cite
|
Sign up to set email alerts
|

Charge Carrier Generation and Transport in Different Stoichiometry APFO3:PC61BM Solar Cells

Abstract: In this paper we studied carrier drift dynamics in APFO3:PC61BM solar cells of varied stoichiometry (2:1, 1:1, and 1:4 APFO3:PC61BM) over a wide time range, from subpicoseconds to microseconds with a combination of ultrafast optical electric field probing and conventional transient integrated photocurrent techniques. Carrier drift and extraction dynamics are strongly stoichiometry dependent: the speed of electron or hole drift increases with higher concentration of PC61BM or polymer, respectively. The electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 45 publications
5
40
0
Order By: Relevance
“…

mixture of electron donating and accepting materials-a bulk heterojunction (BHJ). [8] The effect of donor-acceptor mixing (or phase purity) on charge transport has been previously addressed using microstructural characterization, [9,10] steady-state, [11][12][13] and/or timeresolved [14][15][16] mobility measurements on BHJs with a varying donor-acceptor stoichiometry and/or processing conditions. The coexistence of neat and mixed donoracceptor domains is thought to be beneficial as it could provide an energy cascade [4,5] for charge separation, [6,7] followed by charge transport in the neat phases.

…”
mentioning
confidence: 99%
“…

mixture of electron donating and accepting materials-a bulk heterojunction (BHJ). [8] The effect of donor-acceptor mixing (or phase purity) on charge transport has been previously addressed using microstructural characterization, [9,10] steady-state, [11][12][13] and/or timeresolved [14][15][16] mobility measurements on BHJs with a varying donor-acceptor stoichiometry and/or processing conditions. The coexistence of neat and mixed donoracceptor domains is thought to be beneficial as it could provide an energy cascade [4,5] for charge separation, [6,7] followed by charge transport in the neat phases.

…”
mentioning
confidence: 99%
“…Our results are also applicable to small molecule donors and pristine fullerenes. It has been recently experimentally demonstrated that mainly electron motion in PCBM is responsible for the initial evolution of the charge separation process – hole motion is significantly slower51112. Therefore, in our treatment we consider the hole to be immobile.…”
mentioning
confidence: 99%
“…The first report of charge generation in PPV/C 60 blends [21,91] was interpreted as evidence for immediate charge generation, presumably at domains where order was strong enough to allow for formation of delocalized charges. [96] The transients were also studied with THz methods. The responses over the timescale of ps and ns are highly dependent on the materials systems studied.…”
Section: Photogeneration Of Charge In Donor-acceptor Bulk Heterojunctmentioning
confidence: 99%